Women and Civility in British Politics: Reflections on a Changing Environment. Issue 1 (8th November 2021) - Peele, Gillian
Abstract: The last decade has seen mounting evidence of intimidation in British public life involving threatening behaviour towards and the abuse of public figures, especially MPs and parliamentary candidates. The killings of two MPs (Jo Cox and Sir David Amess) have highlighted the seriousness of this development for the health of British democracy. The article examines the problem using the Committee on Standards in Public Life's 2017 report, Intimidation in Public Life . It explores the possible causes of the decline in civility in British public life, and examines possible remedies for addressing the problem. It argues that the decline of civility and the coarsening of political life reflect a multifaced problem and that, in addition to new measures, such as providing MPs with enhanced security and strengthening protections against online harms, wider long‐term changes to our political culture are necessary to promote civility and tolerance and to foster values that reinforce liberal democracy.